Bipyridyl/carbazolate silver(I) and gold(I) N‐heterocyclic carbene complexes: A systematic study of geometric constraints and electronic properties. (20th December 2019) - Das Adhikary, Sirsendu; Mondal, Ambarish; Kisan, Hemanta K.; Bielawski, Christopher W.; Dinda, Joydev
Abstract : A series of silver(I) and gold(I) carbene complexes of the type [M(L)(2, 2′‐bipyridine)][PF6 ] (L = 1‐benzyl‐3‐(2‐pyridylmethyl)benzimidazolylidene; M = Ag (1 ); M = Au (3 )) and [M(L)(carbazole)] (M = Ag (2 ); M = Au (4 )) were synthesized and analyzed using a range of spectroscopic and crystallographic techniques. Inspection of the solid‐state structures of 1, 2 and 4 revealed a number of intermolecular noncovalent interactions. In the solid‐state structure adopted by 1, π–π and Ag–Ag interactions directed the complexes to orient in a head‐to‐tail fashion. The photophysical properties were found to be influenced by the ancillary ligands in solution as well as in the solid‐state. Calculations were performed to support the aforementioned structural and optoelectronic assignments. Abstract : The synthesis, structures and photophysical properties of a series of Ag(I)/Au(I) complexes supported by 1‐benzyl‐3‐(2‐pyridylmethyl)benzimidazolylidene and either 2, 2′‐bipyridine or carbazole are described. The structures of the complexes are elucidated in solution and in the solid‐state. The photophysical properties are elucidated through a series of experimental and computational techniques and found to strongly depend on the nature of the ancillary ligands.